Visitor Management Information System during the Covid-19 Pandemic - Fauzan; Basar, Abdul Rohmad; Olva, Maria; Hendro Wahyudiono, Pratiwi; Iksan, Nur; Yani, Achmad (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
PT. Epson Batam (PEB) adalah perusahaan multinasional dengan jumlah karyawan lebih dari 3000 orang. Banyaknya tamu (non-karyawan) yang datang ke PT. Epson Batam setiap harinya seperti kunjungan dari instansi pemerintah, partner perusahaan, vendor dan supplier, menyebabkan adanya kebutuhan terhadap aplikasi khusus yang dapat memudahkan perusahaan dalam mengelola data-data para tamu yang berkunjung ke perusahaan dan memudahkan pihak pengaman perusahaan dalam melakukan pencatatan dan rekap tamu yang berkunjung. Penelitian ini bertujuan untuk merancang sebuah sistem informasi pengelolaan pengunjung di masa pandemik Covid-19. Berdasarkan maklum balas dari pengguna disimpulkan bahwa sistem yang dibangunkan bisa digunakan dan berfungsi dengan baik tetapi perlu pengembangan yang memungkinkan sistem informasi terintegrasi dengan alat pengukur suhu. Visitor Management Information System during the Covid-19 Pandemic Abstract: PT. Epson Batam (PEB) is a multinational company with more than 3000 employees. The number of guests (non-employees) who come to PT. Epson Batam every day such as visits from government agencies, company partners, vendors and suppliers, causes the need for special applications that can make it easier for companies to manage the data of guests who visit the company and make it easier for company security to record and recap guests who visit the company. This study aims to design a visitor management information system during the Covid-19 pandemic. Based on the feedback from users, it is concluded that the system developed can be used and functions well but needs development that allows an integrated information system with temperature measuring devices. Keywords: Covid-19, Information System, Management Visitor.